As crianças em suas relações com a música no recreio escolar - Scarpellini, Maira Andriani (2013)
This research was aimed at comprehending the relationship that students establish with the music in a playground. From this objective, we sought to understand what are (and how happen) the musical practices of children in this environment, what are the means used by them to make present this music in the playground, how they teach and learn music at this time of the school routine, how do they share (or not) the music with colleagues and how is the playground organization as a leisure place while at school, with different logics and dynamics. Therefore, it was important to understand the structure and organization of playground, how music weaves times and spaces in that place, how children learn/teach music while play and do other activities in that educational space/time. With a qualitative approach, the method adopted was the case study, and the data collection procedures were based on observations and interviews. We adopted the theoretical principles of the following authors: to understand the playground as a social space, Bourdieu (1997, 2004); to understand it as a space of leisure and learning, Marcellino (1990, 1998, 2006) and Dumazedier (1994); to reflect on the learning as a form of relating to the world, Charlot (2000); and to comprehend the play and playful, Brougère (2001, 2004, 2010, 2012a, 2012b). According to the conclusions, it is detached that children relate to music in a playground in different ways, using portable stereos, singing and percussion to makes it presented in the school. They teach and learn music through play and other forms of interaction such as conversation, singing and percussion. Studying this period the school routine was enriching to address the processes of teaching and learning music for children and thereby to understand the music and pedagogical practices at school.